(3eSGFd GdWhSjs - (3GdWhSj, CHh LYaQ, eMeO Hf GdMSf Hf Ydj, J (B460(3g`s ((3YHO GdeLjO Hf GdgGOj jf GdYHGS Hf Ydjs)
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejf(B... (3hHYO agPg KdGKhf eSCdI CKHJgG GdEeGe GdTjN CHhLYaQ GdWhSj (B...s
(3BNQgG (B:s
(3hGdfcGM Mb hUOb gPG GYJbGOj(B... (3hUdi Gddg Ydi eMeO hBdg(B...s
(3JHUQI GdYfhGf (B:s
(3dYdg(B: (3KdGKhf eSCdI aj ePgH GdTjYIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: (3L(B6(3, U(B84s
(3gOjI GdYGQajf(B: (3L(B2(3, U(B72s
(3GdCYdGe(B: (3L(B6(3, U(B85s
Keywords: (3GdJhMjO hGdedd hGdfMds